Structure-Function Analysis of STING Activation by c[G(2′,5′)pA(3′,5′)p] and Targeting by Antiviral DMXAA - Gao, Pu (Cell, 2013)
Binding of dsDNA by cyclic GMP-AMP (cGAMP) synthase (cGAS) triggers formation of the metazoan second messenger c[G(2′,5′)pA(3′,5′)p], which binds the signaling protein STING with subsequent activation of the interferon (IFN) pathway. We show that human hSTING(H232) adopts a ‘‘closed’’ conformation upon binding c[G(2′,5′)pA(3′,5′)p] and its linkage isomer c[G(2′,5′)pA(2′,5′)p], as does mouse mSting(R231) on binding c[G(2′,5′)pA(3′,5′)p], c[G(3′,5′)pA(3′,5′)p] and the antiviral agent DMXAA, leading to similar ‘‘closed’’ conformations. Comparing hSTING to mSting, 2′,5′-linkage-containing cGAMP isomers were more specific triggers of the IFN pathway compared to the all-3′,5′-linkage isomer. Guided by structural information, we identified a unique point mutation (S162A) placed within the cyclic-dinucleotide-binding site of hSTING that rendered it sensitive to the otherwise mouse-specific drug DMXAA, a conclusion validated by binding studies. Our structural and functional analysis highlights the unexpected versatility of STING in the recognition of natural and synthetic ligands within a small-molecule pocket created by the dimerization of STING.